The benefit of amplification on auditory working memory function in middle-aged and young-older hearing impaired adults - Doherty, Karen A.; Desjardins, Jamie L. (Frontiers in Psychology, 2015)
Untreated hearing loss can interfere with an individual’s cognitive abilities and intellectual function. Specifically, hearing loss has been shown to negatively impact working memory function, which is important for speech understanding, especially in difficult or noisy listening conditions. The purpose of the present study was to assess the effect of hearing aid use on auditory working memory function in middle-aged and young-older adults with mild to moderate sensorineural hearing loss. Participants completed two objective measures of auditory working memory in an aided and unaided listening condition over a six-week trial period with hearing aids. An aged matched control group followed the same experimental protocol except they were not fit with hearing aids. All participants’ aided scores on the auditory working memory tests were significantly improved after wearing hearing aids for six weeks. Thus, using hearing aids in the early stages of age-related hearing loss can improve auditory working memory performance.